2013
DOI: 10.1007/s12517-013-1086-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TSP Loads during the Middle East Springtime Dust Storm (MESDS) in Western Iran

Abstract: In this article, the relation between meteorological parameters and dust activities in western Iran has been studied. Satellite-based data achieved from TOMS are used to investigate the dust activities within a time period of 30 years. In the rst part of this study, we examine the statistical trend of Aerosol Index (AI) and local meteorological parameters in 15 diierent stations. The same patterns of AI variations in all stations indicate that this region has always been subjected to dust storms which originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…The highest correlations are shown in July and August when dust activity is maximal over SW Asia (Rashki et al, 2012), while significant correlations are also detected over Rub-Al-Khali and Oman deserts in June. In contrast, low-to-negligible and slight negative correlations are shown over most parts of Arabia, Syria/Iraqi plains and central-western Iran (here, AI results oppose IDDI retrievals), which are mostly affected by dust storms driven by the Shamal winds that have a different genesis source and meteorological pattern (Masoumi et al, 2013;Najafi et al, 2014;Jish Prakash et al, 2014;Notaro et al, 2015). The negative correlations (r in the range − 0.4 to − 0.5) over Turkmenistan and Karakum Desert (opposite to IDDI retrievals) may be attributed to subsidence as a result of increase in MSLP for the high CasHKI modes (Fig.…”
Section: Karakummentioning
confidence: 68%
See 1 more Smart Citation
“…The highest correlations are shown in July and August when dust activity is maximal over SW Asia (Rashki et al, 2012), while significant correlations are also detected over Rub-Al-Khali and Oman deserts in June. In contrast, low-to-negligible and slight negative correlations are shown over most parts of Arabia, Syria/Iraqi plains and central-western Iran (here, AI results oppose IDDI retrievals), which are mostly affected by dust storms driven by the Shamal winds that have a different genesis source and meteorological pattern (Masoumi et al, 2013;Najafi et al, 2014;Jish Prakash et al, 2014;Notaro et al, 2015). The negative correlations (r in the range − 0.4 to − 0.5) over Turkmenistan and Karakum Desert (opposite to IDDI retrievals) may be attributed to subsidence as a result of increase in MSLP for the high CasHKI modes (Fig.…”
Section: Karakummentioning
confidence: 68%
“…For example, the passage of frontal systems and the east-Mediterranean trough pressure gradient are associated with dust activity over Middle East and Arabia (Hamidi et al, 2013;Awad and Mashat, 2013, in press), while the Indian thermal low and the Levar wind are responsible for dust emissions over SW Asia (Alizadeh Choobari et al, 2014;Kaskaoutis et al, 2015a). However, assessing the atmospheric circulation patterns, which are associated with modulation and long-term trends in dust activity over Middle East and SW Asia has not been evaluated so far except for some case studies (Maghrabi et al, 2011;Najafi et al, 2014;Jish Prakash et al, 2014). Changes in the wind regime between contrasting monsoon years associated with variations in the El-Nino Southern Oscillation (ENSO) seem to affect the dust outflow over the Arabian Sea (Abish and Mohanakumar, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…From the mineralogical point of view, the falling dust contains quartz, calcite, dolomite, carbonate, feldspar, clay, and others. Carbonates and quartz are the major components in Kuwait (Al-Dousari and Al-Awadhi, 2012) and calcite and quartz in western Iran (Najafi et al, 2014). The recent surface deposits are considered as the local source of sand and dust storms, which have acute environmental hazards on public health, life quality, and the State's economy (Al-Hurban, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the most common method to study the dust storms in Iran is to use the ground‐based measurements and meteorological stations data. The study of the frequency, temporal changes of particulate concentration, and determination of the statistical parameters of dust events in southeast (Rashki, deW Rautenbach, et al, ), southwest (Azizi et al, ; Shahsavani et al, ; Zarasvandi et al, ), and whole of Iran (Alizadeh Choobari et al, ); the evaluation of the effect of meteorological conditions on dust storms in Ahwaz (Shahsavani et al, ) and Sistan plain (Rashki et al, ); the determination of the elemental, mineral, metal, and microbiological compounds of mineral dust aerosols in western and southwestern cities (Najafi et al, ; Shahsavani et al, ; Zarasvandi et al, ); the classification of the areas prone to dust production based on geological and precipitation maps in the Middle East (Gerivani et al, ) and the study of the effect of land use changes of Hamun basin on dust storm created in Sistan plain (Rashki, Kaskaoutis, et al, ) were among the subjects studied by analyzing the data of in situ measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Because of high price of measuring instruments in ground‐based stations and limited time covering of remote sensing method, nowadays using numerical modeling has become a common method in research studies. For example, to determine dust sources and the contribution of each source in dust events coming toward the western areas (Ashrafi et al, ; Boloorani et al, ; Najafi et al, ; Sotoudeheian et al, ) as well as big cities of central Iran (Ashrafi et al, ; Givehchi et al, ; Sotoudeheian et al, ) and to specify the movement pattern of the aerosols raised from Sistan plain in southeast of Iran (Rashki et al, ), Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model was used. The results of Najafi et al () study showed that the main sources of dust entering the western areas of Iran are the dry rivers and lakes bed, alluvial deposits, and deserts of Iraq especially the Tigris and Euphrates basins, Hoor al‐Azim wetlands, and the deserts of north and northeast of the Arabian Peninsula as well as south and southeast of Syria.…”
Section: Introductionmentioning
confidence: 99%